Effect of oxide layer and the duration of exposure on the liquid metal corrosion mechanism of RAFM steel in molten Pb-Li. (1st May 2021) - Chakraborty, P.; Naveen Kumar, N.; Sai Krishna, N.; Maheshwari, N.K.; Bysakh, S.; Bose, A.; Kain, V.; Tewari, R.
Highlights: IN-RAFMS corroded at 159.4 μm/y in molten Pb-Li (stirring conditions) for 10, 000 h via selective dissolution of Fe and Cr. Incubation Period depicted low corrosion rate due to grain boundary attack and oxide dissolution. Cr23C6 precipitates at the grain/lath boundaries weakens oxide layer leading to Pb-Li ingress. CFD confirmed higher velocities at greater radial distance which reduce grain boundary attack but cause grain dropping. Complete dissolution of oxide layer changes the mechanism to matrix dissolution. Abstract: The long-term corrosion behavior of IN-RAFM steel in molten Pb-Li upto 10, 000 h of exposure was studied in a rotating disc corrosion test facility at 823 K. As-received IN-RAFMS material possessed an air-formed surface layer containing oxides of Fe, Ce and W. Precipitation of chromium carbides at the grain/lath boundaries of as-received IN-RAFMS led to grain boundary attack by liquid Pb-Li during the initial "Incubation Period" which depicted slow dissolution of surface oxides and lesser corrosion rate. Complete dissolution of oxide layer altered the corrosion mechanism from grain boundary attack to matrix dissolution thereby increasing the corrosion rate.